TRANSFORMASI PEMBELAJARAN PESANTREN: OPTIMALISASI DAYA PIKIR KREATIF SANTRI MELALUI MIND MAPPING - Mimi Hilmiah; Syamsul Aripin (Jurnal Studi Pesantren, 2025)
Education in the modern era faces major challenges in developing students understanding and creativity amidst limited resources and time. One potential solution that can improve the quality of learning is the mindmapping method, which is known to help students organize ideas and information visually, thereby improving their understanding and creativity. This study aims to explore the effectiveness of using mindmapping in learning, with a focus on its influence on students' understanding of the material and creativity. The method used in this study is a qualitative approach with library research, where data is obtained from journal articles, books, and other relevant sources that discuss mindmapping in the context of education. The results of the discussion show that mindmapping has proven effective in facilitating students' understanding of the concepts taught and stimulating their creativity in solving problems. By using visualization techniques, students can connect various ideas and information that were previously separate. The conclusion of this study confirms that mindmapping is an effective method for improving students' understanding and creativity, and can be applied in various learning contexts to support students' cognitive and creative development. This study also provides recommendations for educators to integrate mindmapping into their teaching methods.